Infant mortality inequities for Māori in New Zealand: a tale of three policies - Christopher Rutter; Simon Walker (BMC, 2021)
Abstract Background The history of infant mortality inequities among Māori in New Zealand provides a remarkable case study for understanding the shortcomings of policy which fails to consider the differential risks associated with disadvantaged groups. Specifically, the failure of the initial 1991 reform in addressing Māori infant health, followed by the relative success of post-1994 policy, demonstrate that disadvantaged populations carry differential social risks which require adjusting policy accordingly. Literature on these policies show that differential risks may include disparities in representation, access to resources, socioeconomic status, and racism. The consideration of differential risks is important in analyzing the underlying causes of inequities and social policy deficiencies. Aim To describe and illustrate the need for policy addressing inequities to consider the differential risks associated with disadvantaged groups through an analysis of New Zealand's Māori infant mortality policy progression. Methods The article is a commentary on a series of policies aimed at reducing infant mortality in New Zealand. It analyses three policies and how their differences are linked to the corresponding trends in equity between Māori and non-Māori populations. Findings The progression of Māori infant mortality policy clearly demonstrates that equitable social policy must be culturally sensitive and inclusive towards disadvantaged groups, as well as willing to adapt to changing circumstances and shortcomings of current policy. Prior to 1994, health policy which did not account for the differential risks of Māori populations caused inequities in infant mortality to increase, despite infant mortality decreasing on a national level. After policy was adjusted to account for Māori-specific risks in 1994, infant mortality inequities significantly declined. A comprehensive analysis of these policies shows that the consideration of differential risks is highly related to a decrease in corresponding inequities. Conclusions As New Zealand, and other countries facing inequities such as the United States and Australia, move forward in constructing policy, they would do well to consider the lessons of how New Zealand policy changed the frequency of infant mortality in Māori populations. The study shows that the consideration of differential risks associated with disadvantaged groups is necessary for policy to successfully address inequities.